Development and Evaluation of a Complexity Measure for the Work of Assembly Teams - Latos, Benedikt; Kalantar, Peyman; Burgert, Florens; Arend, Matthias; Nitsch, Verena; Przybysz, Philipp; Mütze-Niewöhner, Susanne
The demand for individualized products increases the complexity in assembly. This poster presents the development of a complexity measure for the work of assembly teams that work in One-Piece-Flow assembly systems. It is based on the Shannon Entropy complexity measurement approach. The measure is implemented into a 3D simulation model. Moreover, the results of simulation studies are presented that were conducted to evaluate the measure. Finally, the results are discussed and further research steps of implementing the measure into a Digital Twin of the assembly line are conceptualized.